The Role of Psychological Flexibility in the Treatment of Anxiety Disorders: A Systematic Review - P. Bijulakshmi; V. Veera Balaji Kumar (Archives of Medicine and Health Sciences)
Anxiety disorders are the most prevalent among psychiatric disorders, and adequate knowledge about the development and treatment of anxiety disorders is essential. Psychological flexibility (PF) is the dynamic process wherein an individual can adapt to situational demands while handling stressful situations and has been postulated to be related to the development of anxiety disorders. This systematic review analyzed the concept of PF in relation to the development and treatment of anxiety disorders. The keywords “psychological flexibility in the treatment of anxiety disorders” were used to search the databases PubMed and Google Scholar. Articles from 2012 to 2022 were included. Results were categorized into two groups, Group 1 consisted of articles that studied the relationship of PF to anxiety disorders in a clinical perspective and Group 2 consisted of articles that explained the role of PF in anxiety in a theoretical perspective. Group 1 consisted of 53 articles that included studies on the role of PF in anxiety disorders; out of which 31 were randomized clinical trials on the efficacy of increasing PF in the treatment of anxiety disorders. Group 2 consisted of 39 articles that explained the role of PF in the formation of anxiety and in maintaining mental health. Research findings have shown that PF is a process wherein individuals can learn to navigate negative emotions and strive to achieve valued goals in the face of adversities by regulating behavioral patterns. Thus, PF plays an important role in psychological well-being and hence has a therapeutic role in the treatment of anxiety disorders.